What have we learned? ten years on - Härtel, Charmine E. J., 1959-; Ashkanasy, Neal M., 1945-; Zerbe, W. J. (Research on emotion in organizations ;, 2011)
The theme of this volume, What Have We Learned? Ten Years On, provides a wonderful tour of the ways in which emotions research has advanced the way in which we conceive of work and its possibilities for adding value to life. The volume is presented in eight parts, so that the reader will can how emotions research has advanced our knowledge and understanding of what comprises work, the experiences and resourcefulness of traditional and non-traditional workers, the drivers of consumer behavior, the dynamics of team behavior, the quality of the leader-member relationship, the demands and skills required of In Extremis work contexts, methods to improve noncognitive assessment, and advances in ways to create and maintain Positive Work Environments. The chapters in this volume leave no doubt in the readers mind that emotions as energizing and motivating mechanisms demand understanding and attention in order to improve performance and societal value from organizational activities, ensure dignity for workers and consumers, and create workplaces where individuals are engaged and flourishing.